Worklife expectancies of fixed-term Finnish employees in 1997–2006 - Nurminen, Markku (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'Fixed-term employment is prevalent in the Finnish labor force. This form of employment contract is marked by fragmentary work periods, demands for flexibility in workhours, and concern for multiple insecurities. A nonpermanent employee may also incur adverse health consequences. Yet there exist no exact statistics on the duration of fixed-term employment. This paper estimated the future duration of the time that a Finn is expected to be engaged in irregular work. ' ' METHODS ': 'Multistate regression modeling and stochastic analysis were applied to aggregated data from surveys conducted among the labor force by Statistics Finland in 1997–2006. ' ' RESULTS ': 'In 2006, a Finnish male was expected to work a total of 3.8 years in fixed-term employment, combined over consecutive or separate time spans; this time amounts to 8% of his remaining work career from entry into the work force until final retirement. For a woman the expectancy was greater, 6.5 years or 13%. For the age interval 20–29 years, the total was 16% for men and 23% for women. ' ' CONCLUSIONS ': 'The type and duration of employment is influenced by security factors and economic cycles, both of which affect men and women differently. Over the past decade, fixed-term employment increased consistently in the female labor contingent, and it was more pronounced during economic slowdowns. This labor market development calls for standards for flexibility and guarantees for security in the fragmented future worklives of fixed-term employees.
Keywords: employee; employment contract; Finland; fixed-term employment; labor force statistics; worklife expectancy; workplace relations